Lao People's Democratic Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
Progress in fiscal reforms, especially with regard to revenue mobilization, will require a broader reform of center-province fiscal relations in Lao People's Democratic Republic. There are challenges ahead to restructure the state-owned commercial banks (SCB) and strengthen the banking system. Corporate governance of SCBs is still weak, hampered by the absence of a fully independent board of directors. The international advisors should continue to play an important role in the bank restructuring process. The note presents statistical data on economic indices of Lao People's Democratic Republic.